Clinical Nurse Leader Knowledge Production to Quality Improvement in a Seamless Trajectory: A Participatory Research Approach. Issue 4 (October 2019) - Bender, Miriam; Spiva, LeeAnna; Patrick, Sara; Meffert, Sarah; Moton, Lonnie; Clarke, Sharee; Mathis, Kendra; Leclerc, Lucy; Knotts, Kimberly; Mount, April
Abstract : Background: Health systems are actively implementing Clinical Nurse Leader (CNL)-integrated care delivery across the United States. Problem: However, the CNL model is a complex health care intervention, making it difficult to generate evidence of effectiveness using traditional research frameworks. Approach: Participatory research is a growing alternative to traditional research frameworks, emphasizing partnership with target community members in all phases of research activities. This article describes a system-based participatory study that leveraged academic and practice knowledge to conduct research that was feasible and relevant, and which produced findings that were easily translated into systematic action by the health system. Outcomes: Study data were used to produce improvements in the health system's CNL onboarding process, role differentiation, performance, recruitment, and growth plus development. Conclusions: A participatory approach can be used in future CNL studies, providing a framework for research efforts and potentially speeding up CNL evidence generation and utilization in practice. Abstract : Supplemental Digital Content is Available in the Text.